Bone marrow-targeted thrombopoietin delivery via engineered platelet-derived vesicle-loaded dissolving microneedles for treating ionizing radiation-induced injury - Zhenchao Ma; Yuntao Li; Jiawei Zhu; Sheng Qiu; Yingrong Chen; Hengbin Cao; Shuixin Yang; Xueli Jia; Lixia Huo; Qian Shi; Shunwen Han; Hao Chang; et al. (Materials Today Bio)
Exposure to a nuclear accident or a radiological attack may cause serious death events due to hematopoietic acute radiation syndrome (H-ARS). While thrombopoietin (TPO) shows promise in mitigating myelosuppression, its clinical use is restricted due to high doses, strict schedules, and systemic toxicity from conventional administration. This study developed a dissolving microneedle patch loaded with engineered activated platelet-derived vesicles encapsulating TPO (TLEVs@MN) for targeted treatment of H-ARS. Activated platelet-derived vesicles were isolated via ultracentrifugation and then modified with glutathione. Glutathione-based anti-ROS modification effectively protected vesicles from radiation-induced oxidative damage, enhancing their stability and targeting efficiency. Using mild sonication, TPO was efficiently encapsulated into engineered vesicles without compromising membrane protein integrity. Further loading into dissolving MNs facilitated minimally invasive transdermal delivery while ensuring long-term vesicle stability during storage. TLEVs@MNs effectively activated the JAK2/STAT3 pathway, restoring mitochondrial function in hematopoietic stem cells. Pharmacokinetic and biodistribution analyses demonstrated that administration of TPO using TLEVs@MNs achieved the precise TPO delivery to bone marrow hematopoietic stem and progenitor cells, significantly improving survival rates and hematopoietic recovery in irradiated animal models. These findings highlighted TLEVs@MN patch as a promosing and robust TPO delivery platform for managing IR-induced hematopoietic injury.